PENGARUH MODEL PROBLEM BASED LEARNING PADA MATERI WUJUD ZAT DAN PERUBAHANNYA TERHADAP KEMAMPUAN BERPIKIR REFLEKTIF SISWA KELAS IV DI SEKOLAH DASAR - Septiani Wicaksono, Itsna; Rosmiati; Triman Junarsiono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Reflective thinking is important for students, especially during the learning processbecause it is used to support students so that they can more easily understand thematerial and can can be optimally involved. The results of interviews with teachersthat there are still learning difficulties, one example is students who are difficult tocondition and have not implemented student reflective thinking. This study wasconducted with the aim of analyzing the effect of applying the Problem BasedLearning (PBL) model on the reflective thinking ability of grade IV students on thematerial of the form of substances and their changes. This research was conductedat SDN Dr. Sutomo 5 Surabaya. Using Descriptive qualitative methods and datacollection using observation, tests, and questionnaires. Based on the analysis of theaverage value of experimental class 1 is 83.2 and the value of experimental class 2is 81.2. The results of the t test analysis of experimental class 1 obtained pretestand posttest with t count 11.35> t table 2.06 and p-value 0.00 <0.05. Meanwhile, theexperimental class 2 obtained t count 7.53 > t table 2.06 and p-value 0.00 < 0.05.Furthermore, the N-Gain value of experimental class 1 is 0.60 and experimentalclass 2 with an average of 0.54. The results of student responses show thatexperimental class 1 is superior in understanding, while experimental class 2 issuperior in understanding and habitual action. It can be concluded that the problembased learning model has an effect on the reflective thinking skills of fourth gradestudents on the material of the form of substances and their behavior.